Sterritt family papers
Correspondence, articles of agreement, bills including bills of sale for slaves, bonds, notes, inventories, appraisals, wills, and other papers.
Sterritt (Sterrett) family of the clan Stewart (Stuart), who lived at various times in Kentucky and Virginia. Earlier papers utilize Starrett (Sterrett) as the spelling of the family name.
Collection material in English.
Keywords: Scottish Americans -- Kentucky; Scottish Americans -- Virginia; Slave records -- Kentucky; Slave records -- Virginia; Sterrett family; Stuart family; Kentucky -- Social life and customs; Scotland -- Social life and customs; Virginia -- Social life and customs